A dynamic panel analysis of the profitability of Australian tax entities - Feeny, S.; Harris, Mark; Rogers, M. (PHYSICA-VERLAG GMBH & CO, 2005)
This paper investigates the determinants of profitability of Australian tax entities using data for 91 different industries over the period 1991/ 92 to 1996/97. A simple oligopoly model is augmented with lagged profitability to allow for persistence of profitability shocks. The Wansbeek-Bekker estimator is used to control for endogeneity of this lagged dependent variable, whilst simultaneously controlling for observed and unobserved entity heterogeneity. Aggregate results suggest that profitability in the previous year, capital intensity, and barriers to entry have the expected positive association with current profitability. Market share - and to a lesser extent concentration - have a U shaped relationship with profitability. © Springer-Verlag 2005.